Influence of Entrepreneurial Orientation, Market Sensing, and Dynamic Capabilities on Competitive Advantage - Mahmuddin, Mahmuddin; Fauzi, Irsal; Uhai, Sabalius; Siagian, Ade Onny (IJBLE Scientific Publications Community Inc., 2026)
This study examines the influence of entrepreneurial orientation, market sensing, and dynamic capabilities on competitive advantage in firms operating within dynamic and highly competitive industries. Using a quantitative research design, data were collected from managerial-level respondents through a structured Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM). The results show that all three constructs significantly and positively affect competitive advantage, with dynamic capabilities demonstrating the strongest influence, followed by entrepreneurial orientation and market sensing. These findings indicate that competitive advantage stems not only from proactive and innovative strategic orientation but also from the firm’s ability to interpret market signals and continually reconfigure internal resources to adapt to environmental shifts. The study contributes to strategic management literature by highlighting the integrative role of entrepreneurial behavior, environmental intelligence, and organizational adaptability in shaping competitive outcomes. Practical implications suggest that managers should cultivate a balanced approach that enhances strategic posture, strengthens market-driven decision-making processes, and builds robust dynamic capabilities to sustain superior performance.